Living donor liver transplantation in hepatocellular carcinoma: A single-center experiences - Ertuğrul, Gökhan; Yanaral, Tumay (Journal of Surgery and Medicine, 2019)
Aim: Hepatocellular carcinoma (HCC) is the most common primary solid tumor of the liver. Hepatitis B virus (HBV) infections, Hepatitis C virus (HCV) infections and at alcoholism can be seen. The aim of this study was to evaluate living donor liver transplantation in hepatocellular carcinoma. Methods: This is a retrospective cohort study. Between April 2014 and December 2017 at Medipol University Medical Faculty Hospital Organ Transplantation Department, 38 patients in living donor liver transplantation for HCC were evaluated. Results: The mean patient age was 58.0 (9.9) (20–74) years; 31 (81.6%) of the 38 were male. The mean MELD score was 14.2 (8–32). Outside Milan criteria (P=0.003), poorly differentiated and cholangiocarcinoma tumor component (P=0.003) appears to be worse in living donor liver transplantation in hepatocellular carcinoma. Conclusions: In this study, outside Milan criteria, poorly differentiated and cholangiocarcinoma tumor component appears to be worse in living donor liver transplantation in hepatocellular carcinoma.